Enteroendocrine Cell Formation Is an Early Event in Pancreatic Tumorigenesis - Caplan, Leah R.; Vavinskaya, Vera; Gelikman, David G.; Jyotsana, Nidhi; Trinh, Vincent Q.; Olive, Kenneth P.; Tan, Marcus C. B.; DelGiorno, Kathleen E. (Frontiers in Physiology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is a devastating disease with a 5-year survival rate of only 11%, due, in part, to late diagnosis, making the need to understand early events in tumorigenesis critical. Acinar-to-ductal metaplasia (ADM), when not resolved, is a PDAC precursor. Recently, we showed that ADM is constituted by a heterogenous population of cells, including hormone-producing enteroendocrine cells (EECs: gamma, delta, epsilon, and enterochromaffin cells). In this study, we employed histopathological techniques to identify and quantify the abundance of EEC subtypes throughout pancreatic tumorigenesis in mouse models and human disease. We found that EECs are most abundant in ADM and significantly decrease with lesion progression. Co-immunofluorescence identifies distinct lineages and bihormonal populations. Evaluation of EEC abundance in mice lacking Pou2f3 demonstrates that the tuft cell master regulator transcription factor is not required for EEC formation. We compared these data to human neoplasia and PDAC and observed similar trends. Lastly, we confirm that EECs are a normal cellular compartment within the murine and human pancreatic ductal trees. Altogether, these data identify EECs as a cellular compartment of the normal pancreas, which expands early in tumorigenesis and is largely lost with disease progression.